2022
DOI: 10.1002/cphc.202200322
|View full text |Cite
|
Sign up to set email alerts
|

Benzenetriimide‐Based Molecular Conductor with Antiferro‐ to Ferromagnetic Switching Induced by Structural Change of π‐stacked Array

Abstract: Benzenetriimide (BTI) is a promising building block for materials chemistry due to its characteristic 3-fold symmetry and redox properties, whereas little is known about its conductive and magnetic properties. In this study, we synthesized three chargetransfer complexes based on N,N',N''-trimethylbenzenetriimide (BTI-Me). One of the complexes contains isolated dimers of BTI-Me radical anion (BTI-Me *À ), while the other two have the infinite π-stacked array of BTI-Me with the formal charge of À 0.5. The latter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…[32][33][34] BTIs can be transformed into radical anions by chemical reduction, representing a new type of stable radicals showing unique magnetic property and conductivity. [35][36][37] The peculiar stability of BTI-radicals (bulky protecting groups are not necessary) was accounted for by the delocalization of spin over the aromatic backbone and the absence of reactive carbon center. Our previous study indicated that BTI radicals show distinct NIR absorption which was ascribed to the transition between singly occupied molecular orbital (SOMO) of the unpaired electron spin and LUMO + 1 orbital.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[32][33][34] BTIs can be transformed into radical anions by chemical reduction, representing a new type of stable radicals showing unique magnetic property and conductivity. [35][36][37] The peculiar stability of BTI-radicals (bulky protecting groups are not necessary) was accounted for by the delocalization of spin over the aromatic backbone and the absence of reactive carbon center. Our previous study indicated that BTI radicals show distinct NIR absorption which was ascribed to the transition between singly occupied molecular orbital (SOMO) of the unpaired electron spin and LUMO + 1 orbital.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study indicated that BTI radicals show distinct NIR absorption which was ascribed to the transition between singly occupied molecular orbital (SOMO) of the unpaired electron spin and LUMO + 1 orbital. [36,37] We envisioned BTI could be a good molecular platform to construct stable chiral radicals. As chiral groups bearing various α-substituents could be readily introduced on the three nitrogen atoms, [32] different interplay of the unpaired electron spin and chirality is anticipated to be modulated (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations